2020
DOI: 10.1182/blood.2020006446
|View full text |Cite
|
Sign up to set email alerts
|

Why do Tregs suddenly disappear in aplastic anemia?

Abstract: The QUAZAR AML-001 maintenance trial: results of a phase III International, randomized, double-blind, placebo-controlled study of CC-486 (oral formulation of azacitidine) in patients with acute myeloid leukemia (AML) in first remission [abstract]. Blood. 2019; 134(suppl 2). Abstract LBA-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In recent years, numerous studies have demonstrated that cellular immunity plays a large role in the development of BM failure in AA [ 12 14 ], such as overactivation of CD8+ killer T-cells [ 15 ] and diminished immunosuppressive function of Tregs [ 16 , 17 ]. In our study, immune dysfunction in the model rats, including the downregulation of the CD4/CD8 ratio, decreased in CD4+CD25+FOXP3+ Tregs and the secretion of inflammatory factors TNF- α and IFN- γ increased, which reflected a negative regulation of haematopoiesis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated that cellular immunity plays a large role in the development of BM failure in AA [ 12 14 ], such as overactivation of CD8+ killer T-cells [ 15 ] and diminished immunosuppressive function of Tregs [ 16 , 17 ]. In our study, immune dysfunction in the model rats, including the downregulation of the CD4/CD8 ratio, decreased in CD4+CD25+FOXP3+ Tregs and the secretion of inflammatory factors TNF- α and IFN- γ increased, which reflected a negative regulation of haematopoiesis [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%